Propella: A numerical tool to investigate various aspects of podded propulsors - Islam, Mohammed F; Liu, Pengfei; Veitch, Brian (Journal of Naval Architecture and Marine Engineering, 2008)
This paper describes the numerical aspects of a research program on podded propulsors, which is being undertaken jointly by the Ocean Engineering Research Centre at Memorial University of Newfoundland, the National Research Council's Institute for Ocean Technology, Oceanic Consulting Corporation, and Thordon Bearings Ltd. The numerical tool is an in-house panel method code, PROPELLA. The code is a low order source-doublet, steady/unsteady time domain panel method code having capabilities to predict hydrodynamic performance of screw propellers with various configurations. Under the research program, the code was extended and used to model the propellers, pod-strut combinations and strut-wake impingement model. Amongst the hydrodynamic issues that have been addressed through numerical predictions were questions regarding the effects of hub taper angle (propeller only case and pod-strut-propeller case), pod-strut configuration (push and pull), geometric variations, azimuthing conditions and pod-strut interactions (wake impingement effect) on podded propeller performance. Predictions were made both in pusher and puller configurations for the pods and reasonable agreement was achieved between the predictions and measurements. The code is being modified to study the podded propulsors' performance at static and dynamic azimuthing conditions. The code is also capable of performing simulations with propellers and bodies like ship hull, underwater vehicles with fins. DOI: http://dx.doi.org/10.3329/jname.v4i2.990 Â Journal of Naval Architecture and Marine Engineering Vol.4(2) 2007 p.73-86